Gelling ability of kefiran in the presence of sucrose and fructose and physicochemical characterization of the resulting cryogels - Zavala, Lucía (2015)
In this work, the influence of sucrose and fructose on the gel-forming capacity of kefiran was investigated as well as the physicochemical characteristics of the resulting gels. The addition of sugar to gel-forming solutions did not alter the pseudoplastic flow properties of kefiran solutions and after one freeze-thaw cycle translucent gels with high water-holding capability were obtained. A highly porous matrix was revealed by microscopy whose pore size varied with sugar concentration. Sucrose and fructose had different effects on the rheological characteristics of sugar-kefiran gels. An increment in the strength of the gels with progressive concentrations of sucrose was evidenced by an increase in the elastic modulus (G’), indicating that sucrose reinforces the binding interactions between the polymer molecules (p ≤ 0.05). A drastic reduction in elastic modulus occurred, however, when 50.0 % w/w sucrose was added to kefiran gels, resulting in less elasticity. In contrast, when fructose was added to kefiran gels, elastic modulus decreased slightly with progressive sugar concentrations up to 10 %, thereafter increasing up to 50 % (p ≤ 0.05). Supplementation with up to 30 % sugar contributed to water retention and increased the viscous modulus. The relative increment in the elastic and viscous moduli elevated the loss tangent (tanδ) depending on the type and concentration of sugar. Sugars (sucrose, fructose) present in the matrix of the polysaccharide networks modified water-polymer and polymer-polymer interactions and consequently changed the gels’ physicochemical characteristics, thus allowing the possibility of selecting the appropriate formulation through tailor-made kefiran cryogels.